The role of multiple-representation-based ‘real’ learning model in the development of students’ metacognitive and problem-solving abilities - Distrik, I Wayan; Saregar, Antomi (Technium Social Sciences Journal, 2022)
This study aims to determine the effect of learning REAL (Reconizing, Explaining, Applying, Looking back) based on multiple representations to build metacognition and problem solving skills in physics education students. The design of this research is the static group pretest-posttest. The total sample of the study was 114 people spread over 2 state universities in Lampung Province, Indonesia, each consisting of an experimental group (n=57) and a control group (n=57). The collected data were both descriptively and inferentially analyzed. A descriptive analysis was performed by grouping and interpreting data into three categories, while an independent samples t-test was used to perform an inferential analysis. The results revealed that there is a significant N-gain difference in metacognition and problem solving abilities between the experimental and control groups. The REAL learning model with multiple representations plays an important role in developing students’ metacognition and problem-solving abilities. The majority of them state that they are delighted and find it easier to understand basic concepts of electricity and magnetism learning materials. Similarly, metacognitive ability plays an important role in developing students’ physics problem solving skills, as evidenced by regression test results of r = 0.71.